Stance, in motion for Biber, and the Forensic Linguistics - Scaramuzzi-Rodrigues, Agnes dos Santos (The ESPecialist, 2015)
This theoretical essay objectively reflects on the notion of stance explained in: Biber and Finegan (1988); Biber et al (1999); Biber (2006a) and Biber (2006b). Our current interest of study involves the fields of Forensic Linguistics and Corpus Linguistics to uncover uses of stance expressions in corpora arising from the criminal sphere of Crimes Against Life, homicidal domestic violence. We divide the study in three parts namely: first, the introduction that presents the general context of the study; second the answer to the questions in this article and finally its completion.